Triboelectrification induced self-powered microbial disinfection using nanowire-enhanced localized electric field - Zheng-Yang Huo (Nature Portfolio, 2021)
Air-transmitted pathogens are a recognized threat to public health. Here, the authors develop a self-powered, rapid disinfection method toward air-transmitted microbes using the localized electric field to damage the outer structures of microbes driven by a triboelectric nanogenerator.